2020
DOI: 10.2147/jpr.s281749
|View full text |Cite
|
Sign up to set email alerts
|

<p>Retrospective Assessment of Salvage to 10 kHz Spinal Cord Stimulation (SCS) in Patients Who Failed Traditional SCS Therapy: RESCUE Study</p>

Abstract: Background and Objectives A randomized clinical trial demonstrated that 10 kHz SCS (10kHz-SCS) therapy is superior to traditional low-frequency SCS (LF-SCS) at 12- and 24-month clinical follow-ups and led to Food and Drug Administration (FDA) approval of the therapy. The results of the study led our practices to trial 10kHz-SCS in patients who had not maintained pain relief with LF-SCS therapy. Here, we report a large set of data from two clinical sites to assess if 10kHz-SCS is an effective salva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…Over the past two decades, in summary, research studies have demonstrated the clinical and statistical efficacy of high-frequency 10 kHz SCS in patients with chronic refractory low back pain with neuropathic pain and post-laminectomy syndrome [49,68], in addition to painful diabetic neuropathy [64,65,69], non-surgical refractory back pain [55,70,71], chronic neck pain [57,58,62,[72][73][74]], chronic regional pain syndrome (CRPS) [75][76][77][78][79], thoracic pain [67], chronic post-surgical pain [66], chronic pelvic pain [63,80], chronic abdominal pain [81], migraine [82,83], as an adjunctive treatment do decrease opioid utilization [54,59,84], and as salvage therapy [85,86]. Among other painful syndromes in which 10 kHz SCS has been studied, painful diabetic neuropathy (PDN) and chronic neck and upper extremity pain have continued to gain clinical and research interest, as well as the use of 10 kHz SCS as a salvage therapy.…”
Section: Fda Approval Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, in summary, research studies have demonstrated the clinical and statistical efficacy of high-frequency 10 kHz SCS in patients with chronic refractory low back pain with neuropathic pain and post-laminectomy syndrome [49,68], in addition to painful diabetic neuropathy [64,65,69], non-surgical refractory back pain [55,70,71], chronic neck pain [57,58,62,[72][73][74]], chronic regional pain syndrome (CRPS) [75][76][77][78][79], thoracic pain [67], chronic post-surgical pain [66], chronic pelvic pain [63,80], chronic abdominal pain [81], migraine [82,83], as an adjunctive treatment do decrease opioid utilization [54,59,84], and as salvage therapy [85,86]. Among other painful syndromes in which 10 kHz SCS has been studied, painful diabetic neuropathy (PDN) and chronic neck and upper extremity pain have continued to gain clinical and research interest, as well as the use of 10 kHz SCS as a salvage therapy.…”
Section: Fda Approval Statusmentioning
confidence: 99%
“…Amirdelfan et al reproduced similar positive outcomes in a prospective design with 10 kHz SCS, reporting 89.2% of subjects with neck pain and 95% of subjects with upper limb pain had at least 50% pain relief from baseline at 12-month follow-up [57]. Recently, Kapural et al conducted a retrospective data review of two clinical sites to access the utilization of 10 kHz SCS as a salvage therapy and found that 81% of the cases reviewed reported at least 50% pain relief upon utilization of 10 kHz SCS as salvage therapy with significantly decrease in opioid utilization at 12 months post-procedure [85].…”
Section: Fda Approval Statusmentioning
confidence: 99%
“…However, there have been salvage reports looking into different therapies, such as 10‐kHz high‐frequency therapy (HF‐10) and dorsal root ganglion (DRG). One study showed that out of 105 patients that failed traditional SCS, 81% achieved greater than 50% pain relief with HF‐10, and almost all exhibited some clinical improvement 8 . Another case report showed sustained pain improves after 8 months when using DRG spinal stimulation in patients with complex regional pain syndrome (CRPS) that had failed traditional SCS 9 .…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that out of 105 patients that failed traditional SCS, 81% achieved greater than 50% pain relief with HF-10, and almost all exhibited some clinical improvement. 8 Another case report showed sustained pain improves after 8 months when using DRG spinal stimulation in patients with complex regional pain syndrome (CRPS) that had failed traditional SCS. 9 The popularized trialing strategy should be more patient centric and this investigation serves as the foundational work.…”
Section: Introductionmentioning
confidence: 99%
“…The first step towards the holy grail is to walk the extra mile for every patient, even for those who do not respond anymore to the initial paradigm. Salvage strategies and algorithms are gaining interest from researchers and clinicians [8][9][10][11][12][13]. Salvage therapy should not only consist of converting patients towards new paradigms but also introducing extra tools to regain freedom and independence in terms of patient empowerment.…”
mentioning
confidence: 99%